2016
DOI: 10.1002/jso.24164
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node identification using superparamagnetic iron oxide particles versus radioisotope: The French Sentimag feasibility trial

Abstract: This new magnetic tracer is a feasible method and a promising alternative to the isotope. It could offer benefits for ambulatory surgery or sites without nuclear medicine departments. J. Surg. Oncol. 2016;113:501-507. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 38 publications
4
88
0
1
Order By: Relevance
“…The noninferiority of SLNB using a magnetic substance and a magnetic probe has been verified in the French Sentimag, Nordic Sentimag trial, Sentimag Multicenter Trial, and Central‐European Sentimag trial, as well as other studies . In those studies, patients received injections of both SPIO and 99m Tc, with or without blue dye.…”
Section: Discussionmentioning
confidence: 87%
“…The noninferiority of SLNB using a magnetic substance and a magnetic probe has been verified in the French Sentimag, Nordic Sentimag trial, Sentimag Multicenter Trial, and Central‐European Sentimag trial, as well as other studies . In those studies, patients received injections of both SPIO and 99m Tc, with or without blue dye.…”
Section: Discussionmentioning
confidence: 87%
“…Three more feasibility studies were excluded owing to lack of an appropriate sample size calculation. Seven articles matched the inclusion criteria and were available for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The sentinel node detection rates per patient range from 94.4 to 98% [8,9,10,11,12,13,14]. A recent meta-analysis [14] including 7 non-randomised studies [8,9,10,11,12,13,14]showed that Sienna+ is non-inferior to standard mapping techniques for sentinel node detection.…”
Section: Superparamagnetic Iron Oxidementioning
confidence: 99%
“…A recent meta-analysis [14] including 7 non-randomised studies [8,9,10,11,12,13,14]showed that Sienna+ is non-inferior to standard mapping techniques for sentinel node detection. There was no difference in detection rate per patient (fixed odds ratio (OR) 1.10; 95% confidence interval (CI) 0.67-1.79; p = 0.71) between Sienna+ and the standard tracer technique.…”
Section: Superparamagnetic Iron Oxidementioning
confidence: 99%